The Child Evaluation Checklist (CHECK): A Screening Questionnaire for Detecting Daily Functional "Red Flags" of Underrecognized Neurodevelopmental Disorders among Preschool Children. (1st December 2019) - Rosenblum, Sara; Zandani, Irit Ezra; Deutsch-Castel, Tsofia; Meyer, Sonya
Abstract : Background . Early identification of invisible comorbid neurodevelopmental disorders, such as specific learning disorders, attention deficit hyperactive disorders, and developmental coordination disorders, is crucial to improving children's daily functional deficits related to executive functions. However, a practical questionnaire to address parents' concerns is lacking. Aims . To develop a reliable and valid assessment tool that can identify young children at risk for invisible underrecognized neurodevelopmental disorders. This article describes the development and standardization of the Child Evaluation Checklist (CHECK). Methods and Procedures . Participants were 186 children aged 3 to 6 years: 91 with suspected invisible neurodevelopmental disorders, and 95 controls with typical development. Parents completed a demographic questionnaire, the CHECK, and the Behavior Rating Inventory of Executive Function-Preschool Version (BRIEF-P). Outcomes and Results . The CHECK's construct validity indicated high internal consistency for each part (Part A: α = .94 ; Part B: α = .90 ) and moderate-to-high consistency for each of Part A's four factors. Significant correlations, as well as significant group differences, were found between the CHECK factors and BRIEF-P scores. Conclusions and Implications . Use of the CHECK allows for timely identification of suspicious ("red flags") invisible neurodevelopmental disorders. It may support parents' sufficient awareness and knowledge to refer their children for comprehensive evaluation and intervention.